2020
DOI: 10.3390/genes11070803
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Expression Analysis of NHX Gene Family under Salinity Stress in Gossypium barbadense and Its Comparison with Gossypium hirsutum

Abstract: Cotton is an important economic crop affected by different abiotic stresses at different developmental stages. Salinity limits the growth and productivity of crops worldwide. Na+/H+ antiporters play a key role during the plant development and in its tolerance to salt stress. The aim of the present study was a genome-wide characterization and expression pattern analysis under the salinity stress of the sodium-proton antiporter (NHX) of Gossypium barbadense in comparison with Gossypium hirsutum. In G. barbadense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 123 publications
2
24
0
Order By: Relevance
“…Moreover, NHX1 regulated Cd 2+ and H + flow during short-term Cd 2+ shock and confirmed that it could enhance tolerance during Cd 2+ stress [44]. Recent studies have shown that NHX2 homologues had a high expression under salinity stress at higher time intervals in G. barbadense and G. hirsutum [45]. The expressions of NHX were up-regulated in root tissues of wheat under salinity stress [46].…”
Section: Roles Of Rscpa Genes In Response To Different Abiotic Stressesmentioning
confidence: 80%
“…Moreover, NHX1 regulated Cd 2+ and H + flow during short-term Cd 2+ shock and confirmed that it could enhance tolerance during Cd 2+ stress [44]. Recent studies have shown that NHX2 homologues had a high expression under salinity stress at higher time intervals in G. barbadense and G. hirsutum [45]. The expressions of NHX were up-regulated in root tissues of wheat under salinity stress [46].…”
Section: Roles Of Rscpa Genes In Response To Different Abiotic Stressesmentioning
confidence: 80%
“…The function of plant vacuole NHX antiporter has been identified and expressed in an exogenous system to enhance the salt tolerance of plants. Akram et al (2020) found that the NHX gene was up-regulated under salt stress, and Yokoi et al (2002) found that AtNHX1 had higher transcript abundance during salt stress ( Yarra, 2019 ). The results indicated that the expression of NHX genes responded to salt stress during plant growth, which played a very important role in plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…A change in membrane permeability destroys the normal operation of transporters, causing plants to absorb additional sodium ions from the environment, affecting the absorption of other ions and causing nutritional imbalance. Na + /H + antiporters play a key role in plant development and tolerance to salt stress ( Akram et al, 2020 ). In response to the external influence on plants, the ions and water in plants are balanced through their own ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transgenic cotton plants expressing AtNHX1 reportedly produce larger biomass and more fibers when treated with 200 mM NaCl in a greenhouse compared with control plants, implying that AtNHX1 can increase cotton salt stress tolerance [ 40 ]. Researchers found that NHX members in cotton could be involved in various developmental processes and stress responses by maintaining the turgor pressure, pH, and ionic homeostasis [ 41 ]. However, the functions of cotton endosomal-type NHX members related to Na + /H + exchange and localization in plant cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%